Bioactivity Study of the C60-L-Threonine Derivative for Potential Application in Agriculture. (26th March 2019) - Panova, Gayane G.; Serebryakov, Evgeny B.; Semenov, Konstantin N.; Charykov, Nikolay A.; Shemchuk, Olga S.; Andrusenko, Elena V.; Kanash, Elena V.; Khomyakov, Yuriy V.; Shpanev, Alexander M.; Dulneva, Larisa L.; Podolsky, Nikita E.; Sharoyko, Vladimir V.
Abstract : The present paper reports data on the biological activity of nanocompositions based on a C60 -L-threonine (C60 -Thr) derivative. These nanocompositions promote the nonspecific resistance of plants to the action of stress factors (ultraviolet radiation, pesticides, and phytopathogens). Additionally, we determined the perspectives of the C60 -Thr adduct application in the cultivation of plants due to the decrease of the pesticide load on the environment. The biological study of C60 -Thr revealed the plant growth-stimulating ability due to its influence on the photosynthetic apparatus activity and antioxidant properties.